Violence against women as discrimination in contexts of criminal violence: The case of feminicide in Medellín and the State of Mexico [Violência em contra das mulheres como discriminação em contextos de violência criminal: o caso do feminicídio em Medellín e o Estado do México] [Violencia en contra de las mujeres como discriminación en contextos de violencia criminal: el caso del feminicidio en Medellín y el Estado de México] (2020)
The increase in violence rates in countries such as Colombia and Mexico has had a differential impact on women, expressed through multiple forms, including its larger scale expression, feminicide. However, its discrimination background has been made invisible by the different actors who hold power, being the most important of them, the State, who, from the regulatory provisions and public policies around the issue, continues to circumscribe the phenomenon to its intimate categories, that is, linking it, mainly, to relationships of affinity and consanguinity. In this regard, in the area of information management on violence against women and feminicide in particular, two fundamental challenges arise: categorization and underreporting. Faced with these, both Colombian and Mexican legislation and public policy have taken important steps; however, in order to attack the structural and symbolic violence that underlies the problem, as the Constitutional Court (2016) affirms in Colombia, it is necessary to integrate the gender perspective into criminal law, thereby making the approach to the test flexible, to allow the introduction of elements of context configurative of gender violence. © 2020 Policia Nacional de Colombia. All rights reserved.